Xoconostle fruit (Opuntia matudae Scheinvar cv. Rosa) by-products as potential functional ingredients. (15th October 2015) - Morales, Patricia; Barros, Lillian; Ramírez-Moreno, Esther; Santos-Buelga, Celestino; Ferreira, Isabel C.F.R.
Highlights: O. matudae fruit by-products could be used as functional ingredients. The epicarp stands out for its high content in tocopherols and phenolic compounds. The epicarp presented also the highest antioxidant activity. The endocarp stands out for its high glucose, citric acid and PUFA contents. Abstract: There is a lack of information on the potential use of xoconostle cultivars as sources of antioxidants for food, pharmaceutical and colorant industries. The aim of this study was to provide a phytochemical characterisation and antioxidant activity evaluation of Opuntia matudae Scheinvar cv. Rosa by-products (epicarp and endocarp mucilage's), in order to evaluate their interest as sources of functional ingredients for human or animal foods. These by-products showed a high content in glucose, citric and linoleic acids, tocopherols, and isorhamnetin- O -(di-deoxyhexosyl-hexoside) (mainly in epicarp), and presented relevant antioxidant properties. The obtained results support the use of O. matudae Scheinvar cv. Rosa agro-industrial by-products as functional food ingredients, namely for antioxidant-enriched formulations, instead of being discarded.